2017
DOI: 10.1097/md.0000000000006491
|View full text |Cite
|
Sign up to set email alerts
|

Does the pancreatic volume reduction rate using serial computed tomographic volumetry predict new onset diabetes after pancreaticoduodenectomy?

Abstract: Volume reduction of the pancreatic tissues following a pancreatectomy can lead to the deterioration of glucose homeostasis. This is defined as pancreatogenic diabetes mellitus (DM). The objective of this study was to investigate the occurrence of new-onset DM (NODM) and evaluate the risk factors, including the pancreas volume reduction rate in patients undergoing pancreaticoduodenectomy (PD).Sixty-six patients without preoperative DM underwent PD for periampullary tumors between August 2007 and December 2012 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
23
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 17 publications
3
23
1
Order By: Relevance
“…Multivariate analysis conducted by Kwon et al in a study population of 225 patients found that patients who were obese (BMI ≥ 25) had increased risk of developing DM post pancreatectomy (OR 1.25; (95% CI: 1.09‐1.43; P = .001). No significant differences were found in the incidence of obesity between DM and non‐DM groups in the remaining studies that assessed for this …”
Section: Resultsmentioning
confidence: 82%
See 4 more Smart Citations
“…Multivariate analysis conducted by Kwon et al in a study population of 225 patients found that patients who were obese (BMI ≥ 25) had increased risk of developing DM post pancreatectomy (OR 1.25; (95% CI: 1.09‐1.43; P = .001). No significant differences were found in the incidence of obesity between DM and non‐DM groups in the remaining studies that assessed for this …”
Section: Resultsmentioning
confidence: 82%
“…Bock et al found the DM group to be significantly younger than the patients that did not develop DM, whilst Kwon et al found the DM group significantly older. Hwang et al, Kang et al, Shirakawa et al, Wu et al, You et al and Yun et al found no significant differences in age between the two groups.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations